The effect of knowledge sharing on technology acceptance among physicians - Esmaeilzadeh, Pouyan; Sambasivan, Murali; Kumar, Naresh; Nezakati, Hossein (Global Advanced Research Journals, 2013)
The healthcare sector has utilized a variety of technologies such as clinical IT to improve effectiveness of healthcare professionals and the quality of health care delivery. Having unused clinical IT appears a strict challenge for hospitals. Meanwhile, there is enough evidence to state that healthcare professionals have not fully adopted and used clinical IT. The main objective of this study is to identify factors which influence healthcare professionals’ adoption of clinical IT. This study comes up with a modified technology acceptance model (TAM) to integrate both the special characteristic of healthcare professionals and unique feature of clinical IT. This study investigates whether attitude toward knowledge determines healthcare professionals’ intention to use clinical IT. The proposed model has been developed to mainly deal with IT adoption issues among healthcare professionals in hospitals. A survey has been done to evaluate the model among 300 healthcare professionals in Malaysia. The structural equation model has been used to test the model in this context. The results reveal the significant role of perceived threat to professional autonomy, attitude toward knowledge sharing, perceived usefulness and perceived ease of use in shaping healthcare professionals’ intention to use clinical IT in Malaysia. The proposed model can explain 48% of the variance of physicians’ intention to accept clinical IT.